HBXIP, a binding protein of HBx, regulates maintenance of the G2/M phase checkpoint induced by DNA damage and enhances sensitivity to doxorubicin-induced cytotoxicity. Issue 5 (4th March 2017) - Fei, Hongrong; Zhou, Yunsheng; Li, Ruotong; Yang, Mingfeng; Ma, Jian; Wang, Fengze
ABSTRACT: To maintain the integrity of the genome, cells need to detect and repair DNA damage before they complete cell division. Hepatitis B x-interacting protein (HBXIP), a binding protein of HBx (Hepatitis B virus × protein), is aberrantly overexpressed in human cancer cells and show to promote cell proliferation and inhibit apoptosis. The present study is designed to investigate the role of HBXIP on the DNA damage response. Our results show that HBXIP acts as an important regulator of G2/M checkpoint in response to DNA damage. HBXIP knockdown increases phospho-histone H2AX expression and foci formation after treatment with ionizing radiation (IR). HBXIP regulates the ATM-Chk2 pathway following DNA damage. Depletion of HBXIP abrogates IR-induced G2/M cell cycle checkpoints, accompanying decrease the expression of phospho-Cdc25C, phospho-Cdc2 (Tyr15) and p27. We also show that downregulation of HBXIP expression sensitizes cancer cells to chemotherapy, as evidenced by an increase in apoptosis and cleavage of caspase-3 and caspase-9. Our data suggest that HBXIP can function as a mediator protein for DNA damage response signals to activate the G2/M checkpoint to maintain genome integrity and prevent cell death.